1999
DOI: 10.1128/mmbr.63.4.836-843.1999
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral DNA Integration

Abstract: SUMMARY DNA integration is a unique enzymatic process shared by all retroviruses and retrotransposons. During integration, double-stranded linear viral DNA is inserted into the host genome in a process catalyzed by the virus-encoded integrase (IN). The mechanism involves a series of nucleophillic attacks, the first of which removes the terminal 2 bases from the 3′ ends of the long terminal repeats and of the second which inserts the viral DNA into the host genome. IN specifically recognizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(65 citation statements)
references
References 94 publications
0
62
0
3
Order By: Relevance
“…The low number of codons consistent with adaptive evolution within Ogre integrases reduces the probability, but does not exclude the possibility, that Ogre CL5 integrase evolved a new requirement to bind a factor present on recombining chromosomes or that Ogre CL6 and Ogre CL11 lost this requirement and started to insert into all chromosomes including Y. Additionally, we found high conservation of both ends of the LTRs (Fig. 1d), where integrase binds (Hindmarsh & Leis, 1999;Cherepanov et al, 2011), and that the base composition of flanking sequences is identical for all Ogre families, supporting the idea that they share the same integration mechanism and lack of integration site selectivity. The presence of Ogre CL5 in the PAR region and not in other parts of the Y chromosome could alternatively be explained by recombinational transfer from the X chromosome, as PAR regions are subject to an increased probability of crossing-over (Otto et al, 2011).…”
Section: Researchmentioning
confidence: 84%
“…The low number of codons consistent with adaptive evolution within Ogre integrases reduces the probability, but does not exclude the possibility, that Ogre CL5 integrase evolved a new requirement to bind a factor present on recombining chromosomes or that Ogre CL6 and Ogre CL11 lost this requirement and started to insert into all chromosomes including Y. Additionally, we found high conservation of both ends of the LTRs (Fig. 1d), where integrase binds (Hindmarsh & Leis, 1999;Cherepanov et al, 2011), and that the base composition of flanking sequences is identical for all Ogre families, supporting the idea that they share the same integration mechanism and lack of integration site selectivity. The presence of Ogre CL5 in the PAR region and not in other parts of the Y chromosome could alternatively be explained by recombinational transfer from the X chromosome, as PAR regions are subject to an increased probability of crossing-over (Otto et al, 2011).…”
Section: Researchmentioning
confidence: 84%
“…In vitro assays use either Mg 2+ or Mn 2+ as the cofactor in reactions. Mg 2+ is widely considered to be the biological relevant divalent cation cofactor for IN activity in vivo [16][17][18][19] , but IN shows very low activity with Mg 2+ as a cofactor, and Mn 2+ is frequently used in most in vitro assays [8,10,20,21] . We optimized this assay in the presence of either Mg 2+ or Mn 2+ and found that the presence of Mn 2+ instead of Mg 2+ doubled the ST activity, but not as significantly as other reported works in which the Mn 2+ -dependent activity was approximately 4-6 times that of the Mg 2+dependent activity [13,20,21] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, epigenetic marks such as H3 and H4 acetylation are more frequently seen in the integrations sites which suggest that the histone code of the chromatin is probably important for an efficient integration of the HIV-1 genome [64]. The integrase which contains endonuclease activity cleaves the host cell DNA and allows integration to occur [65]. In addition to IN, the key virulence factor Vpr which is introduced in the infected cell along IN, was recently shown to induce DNA damage such as DSB [66].…”
Section: Hiv-1 Integrationmentioning
confidence: 99%